Heading incidence in boys` football over three seasons - Peek, K.; Meyer, T.; Beaudouin, F.; McKay, M. (Science and Medicine in Football, 2021)
Purpose: To quantify the incidence and characteristics of purposeful headers and unintentional head impacts in football (soccer) in boys` football over three seasons. Methods: This retrospective longitudinal study analysed purposeful headers and unintentional head impacts collected over three seasons (under-10 to under-12) using match video analysis from boys` team in Australia. Total headers and head impacts, as well as incidence rate (IR) per 1000 match-hours for different match characteristics, were calculated. Results: Total number of headers and heading IR increased significantly (r = 0.99) with age from under-10 (n = 29; IR: 483) to under-12 (n = 149; IR: 1515). All but three players (87%) were observed to head the ball at least once during a season (mean: 10, range 0-25) with the accumulative number of headers performed by out-field players over three seasons ranging from 6 to 40. Players in defensive positions (n = 121) headed the ball more frequently than midfielders (n = 83) or attackers (n = 53). Five (IR: 22) unintentional head impacts were observed, of which four required medical attention. Conclusion: Although the number of headers performed by young players in under-10 to under-12 age groups was low, the range of headers performed by individuals varied greatly. These results could be used to guide age-specific heading coaching practices.